Deciphering the Supramolecular Organization of Multiple Guests Inside a Microporous MOF to Understand their Release Profile. Issue 18 (17th March 2021) - Balestri, Davide; Mazzeo, Paolo P.; Perrone, Roberto; Fornari, Fabio; Bianchi, Federica; Careri, Maria; Bacchi, Alessia; Pelagatti, Paolo
Abstract: Metal‐organic frameworks (MOFs) give the opportunity of confining guest molecules into their pores even by a post‐synthetic protocol. PUM168 is a Zn‐based MOF characterized by microporous cavities that allows the encapsulation of a significant number of guest molecules. The pores engineered with different binding sites show a remarkable guest affinity towards a series of natural essential oils components, such as eugenol, thymol and carvacrol, relevant for environmental applications. Exploiting single crystal X‐ray diffraction, it was possible to step‐wisely monitor the rather complex three‐components guest exchange process involving dimethylformamide (DMF, the pristine solvent) and binary mixtures of the flavoring agents. A picture of the structural evolution of the DMF‐to‐guest replacement occurring inside the MOF crystal was reached by a detailed single‐crystal‐to‐single‐crystal monitoring. The relation of the supramolecular arrangement in the pores with selective guests release was then investigated as a function of time and temperature by static headspace GC‐MS analysis. Abstract : The stepwise nanoconfinement of mixtures of guest molecules into the pores of a metal‐organic framework is investigated by SC‐to‐SC XRD analyses to understand selective uptake and release at a molecular level. The remarkable site selectivity observed for the incoming guest molecules is crucial to determine the properties of the material and to finely control the release profile.